Advances in intelligent informatics, smart technology and natural language processing : selected revised papers from the joint International Symposium on Artificial Intelligence and Natural Language Processing (iSAI-NLP 2017) /: selected revised papers from the joint International Symposium on Artificial Intelligence and Natural Language Processing (iSAI-NLP 2017). ([2019]) - Unknown
No abstract available